A Forum on the Future of Australia’s NBN - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2019)
The future of the 51 billion Australian National Broadband Network (NBN) remains unknown, with the Government still to commit to a course of action after the current build phase. Industry representatives have recently voiced their concerns about a potential future sale of the NBN and how this would occur. In response, the Telecommunications Association is hosting a public forum on the future of the NBN on 31 July 2019 at RMIT University. Papers in the June 2019 issue of the Journal include discussion on consumer interest in 5G in New Zealand, the history of Australian mail handling and technical papers covering a range of interesting topics. This month we include a paper titled Measuring Digital Inequality in Australia: the Australian Digital Inclusion Index that provides an important insight into digital inclusion. The Journal welcomes further contributions on telecommunications and the digital economy.